2014
DOI: 10.4236/msa.2014.510075
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Five (5) Possible Contaminants in Recycled Cardboard Packages and Food Simulants Using Ultrasound Assisted Extraction Coupled to GC-MS

Abstract: A modified analytical procedure has been developed to test for 5 organic pollutants [benzophenone, 2 diisopropylnaphthalenes (DIPNs) {2,6-and 2,7-diisopropylnapthalene} and 2 hydrogenated terphenyls (HTPs) {m-terphenyl and o-terphenyl}] that can be found as residues in recycled cardboards intended for use as food packaging materials and to test for migration levels of these compounds in a food simulant (Tenax). A main objective was to develop a modified rapid and reliable method for the identification and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…It is shown that evidence of the relevant compounds can be successfully demonstrated. The level of benzophenone determined in this study was more than that obtained for recycled cardboards in Greece (Parigoridi et al, 2014), whereas it is similar to levels which are reported for cardboard used in cartons (Anderson and Castle, 2003). Benzophenone may be sourced from UV-cured inks and lacquers used to print on the packaging.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is shown that evidence of the relevant compounds can be successfully demonstrated. The level of benzophenone determined in this study was more than that obtained for recycled cardboards in Greece (Parigoridi et al, 2014), whereas it is similar to levels which are reported for cardboard used in cartons (Anderson and Castle, 2003). Benzophenone may be sourced from UV-cured inks and lacquers used to print on the packaging.…”
Section: Discussionsupporting
confidence: 76%
“…These kinds of contaminants have harmful effects on biological systems and can cause various diseases and disorders, even in relatively low concentrations (Grosse et al, 2011;McLean et al, 2007;Meeker et al, 2009). To our knowledge, there are few reports on the identification of organic pollutants in dry foodstuff packaging (Bononi and Tateo, 2009;Parigoridi et al, 2014). However, in these studies, the authors found some important organic pollutants in real recycled cardboard samples from various sources.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it is important to use a proper simulant that represents the same properties as the foodstuff. Food simulants like Tenax, water or organic solvents have been used to simulate migration of NIAS from packaging (Bignardi et al, 2017;Bentayeb et al, 2007;Aznar et al, 2016), adhesive formulas (Félix et al, 2012;Canellas et al, 2012), and paper and board FCMs (Suciu et al, 2013;Bradley et al, 2008;Parigoridi et al, 2014). Commission Regulation (EU) No 10/2011 (Annex III) on plastic materials and articles intended to come into contact with food, contains a list of recommended food simulants to be used for certain food types.…”
Section: Nias Extractionmentioning
confidence: 99%
“…Dichloromethane is suitable for extracting DBP because of its non-polar solvent. Parigoridi et al (2014) reported that dichloromethane had the best ability to extract various contaminants from recycled paper while compared with hexane and ethanol. The extracted analyte of the samples further identified with GC-MS.…”
Section: Determination Of Di-butyl Phthalate In Recycled Paperboardmentioning
confidence: 99%
“…Suciu et al (2013) used soxhlet extraction for bisphenol A (BPA), DEHP, nonylphenol mono-ethoxylate (NMP) and nonylphenol diethoxilate (NDP) on recycled paper food packaging. In addition, on recycled food paper, Parigoridi (2014) has conducted an analysis to determine vary type of contaminants that contained therein using UAE extraction method with dichloromethane.…”
Section: Introductionmentioning
confidence: 99%